Impact of the Accounting Information System on Corporate Governance: Evidence from Turkish Non-Listed Companies - Ali Uyar; Ali Haydar Gungormus; Cemil Kuzey (Australasian Accounting, Business and Finance Journal, 2017)
Corporate scandals in the early 2000s have demonstrated how accounting and auditing failures, together with the abuses of managers have the ability to create major problems. In order to avoid future scandals, this study investigates the association between the accounting information system and corporate governance. We hope that these findings will contribute towards the enhancement of good corporate governance created by the accounting function of business organizations. The results of empirical analyses indicate that bookkeeping, financial reporting, and the budgeting system have a positive impact on the corporate governance level, whereas the adoption of Turkish Accounting / Financial Reporting Standards do not. Thus, in order to foster corporate governance, managers should establish internal reporting procedures as well as internal control and monitoring devices before attempting external control through independent auditing.
Keywords: Accounting information system; bookkeeping; financial reporting; accounting standards; corporate governance; management accounting; Turkey